Crystal field splitting on D↔S transitions of atomic manganese isolated in solid krypton - Byrne, O.; Collier, M.A.; Ryan, M.C.; McCaffrey, J.G. (Физика низких температур, 2010)
Narrow excitation features present on the [Ar]3d⁶4s¹ a⁶D(J=9/2–1/2)←[Ar]3d⁵4s² a⁶S1/2 transitions of manganese atoms isolated in solid Kr are analyzed within the framework of weak crystal field splitting. Use of the Wp optical lineshape function allowed identification of multiple zero-phonon lines for individual spin-orbit J states of the a⁶D←a⁶S transition recorded with laser-induced excitation spectroscopy. Excellent agreement exists between the predicted crystal field splitting patterns for the J levels of the a⁶D state isolated in the «red» tetravacancy site of solid Kr. The tetrahedral crystal field of the «red» trapping site splits J>3/2 levels of the a⁶DJ and a⁴D₇/₂ states by approximately 30 cm⁻¹. This report represents the first definitive evidence of crystal field splitting, induced by the weak van der Waals interactions between a neutral metal atom and the rare gas atoms surrounding it in a well defined solid state site.